2018
DOI: 10.1016/j.neuroimage.2018.06.078
|View full text |Cite
|
Sign up to set email alerts
|

Reproducibility of corticokinematic coherence

Abstract: Corticokinematic coherence (CKC) between limb kinematics and magnetoencephalographic (MEG) signals reflects cortical processing of proprioceptive afference. However, it is unclear whether strength of CKC is reproducible across measurement sessions. We thus examined reproducibility of CKC in a follow-up study. Thirteen healthy right-handed volunteers (7 females, 21.7 ± 4.3 yrs) were measured using MEG in two separate sessions 12.6 ± 1.3 months apart. The participant was seated and relaxed while his/her dominant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

5
4

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 26 publications
4
24
0
Order By: Relevance
“…The test-retest intervals in most studies are days to weeks. Recasens et al [47] report results from a 7-week interval and both Piitulainen et al [57] and Dunkley et al [48] report results for intervals greater than one year. Over all the reports, the maximum number of subjects was 40 [46].…”
Section: Test-retest Reliabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…The test-retest intervals in most studies are days to weeks. Recasens et al [47] report results from a 7-week interval and both Piitulainen et al [57] and Dunkley et al [48] report results for intervals greater than one year. Over all the reports, the maximum number of subjects was 40 [46].…”
Section: Test-retest Reliabilitymentioning
confidence: 99%
“…These regions were selected because their baseline vs. 16-month follow-up correlations are typical and their difference values are significantly different from zero and visibly so in the figure . evoked response paradigms [44][45][46][47][48][49][50][51]. For free-running paradigms, most measures are for resting connectivity confined to frequency bands [52][53][54][55][56][57][58]. The test-retest intervals in most studies are days to weeks.…”
Section: Test-retest Reliabilitymentioning
confidence: 99%
“…Studies demonstrated that CKC (i) is detectable in most investigated subjects with high level of coherence compared with, e.g., cortico-muscular coherence (CMC) that is detectable in about 60-70% of the subjects (Pohja et al, 2005), (ii) shows a high degree of inter-session reproducibility at the individual level (Piitulainen et al, 2018), and (iii) is robust against artifacts associated with implanted ferro-magnetic materials providing that the temporal signal space separation method is used to subtract the artifact from raw MEG signals (Bourguignon et al, 2016).…”
Section: Investigation Of Proprioceptive Pathways Using Cortico-kinematic Coherencementioning
confidence: 99%
“…Therefore, the strength of CKC quantifies the degree of cortical proprioceptive processing and has shown to be associated with motor performance (Piitulainen, Seipäjärvi, et al., 2018b). The inter‐session reproducibility of CKC is shown to be excellent at the group level (Piitulainen, Illman, et al, 2018a; Piitulainen et al., 2020). CKC is thus a potential clinical tool to detect, examine and follow deficits in cortical proprioceptive processing, for example, in newborn using EEG (Smeds et al, 2017) or in motor impairments such as Friedreich ataxia using MEG (Marty et al., 2019).…”
Section: Introductionmentioning
confidence: 99%